Turkish Toponymy and Its Stages of Development - Turdibekov Mumin Turayevich (Zien Journals, 2021)
The natural geography of each inhabited area, the linguistic features of the population living here, the name of the place, which appears in accordance with the daily routine, is formed from history. Toponyms as a social process have been passed down from generation to generation as an important stage in historical development. Therefore, in the past, naming a place in our country was never done by the decree or decision of the supreme ruler, but because of the will of the people, the eternal value.
Keywords: toponymy; Turkish names; continent; ocean